Capital consolidation as a means of countering threats of loss of economic sustainability - Fesiuk , Yurii (Ways to Improve Construction Efficiency, 2025)
Capital consolidation is studied as a comprehensive tool for ensuring stable functioning and sustainable development of economic systems of various levels in conditions of increasing uncertainty and risks. The relevance of the study is due to the increasing destabilizing influence of macroeconomic, financial and structural factors that form threats of loss of economic stability of business entities, industry complexes and the national economy as a whole.The purpose of the article is to scientifically substantiate the forms, conditions and scientific and methodological principles of using capital consolidation as an effective tool for countering threats to economic stability in the modern transformation environment. The study applied systemic, structural-functional and hierarchical approaches, which made it possible to consider capital consolidation as a dynamic process of integration of financial, production and organizational-management resources.It has been proven that the impact of capital consolidation is multi-level and is implemented at the micro, meso and macroeconomic levels. At the enterprise level, it contributes to increasing financial stability by optimizing the capital structure, reducing the debt burden and increasing liquidity. At the mesoeconomic level, capital consolidation ensures the formation of business-integrated structures and industry associations that increase the adaptability of regional economic systems and reduce the fragmentation of resources. At the macroeconomic level, it acts as a tool for concentrating investment resources, stabilizing the financial system and coordinating short-term stabilization measures with long-term goals of sustainable development.The effectiveness of capital consolidation as a tool for countering economic threats is determined by a set of conditions, among which the key ones are the quality of the institutional environment, the strategic focus of management decisions, the preventive nature of the application of consolidation and the balance between concentration and diversification of capital; in the absence of appropriate conditions, consolidation may lose its stabilization potential and acquire the characteristics of an additional source of systemic risks.Scientifically based use of capital consolidation creates prerequisites for increasing adaptability and long-term economic sustainability in conditions of growing uncertainty, and also forms a methodological basis for further research aimed at developing applied mechanisms for managing consolidation processes in economic systems of various levels.